L2 learning outcomes of a research-based digital app for Japanese children - Bang, Hee Jin; Setoguchi, Eric; Mackey, Alison; Fujii, Akiko (Studies in second language acquisition, 2024)
Digital educational game-based apps can be effective in helping young children develop language skills, particularly when paired with formal instruction. However, we need to know more about how educational games benefit learning in the absence of formal instruction, given children’s proficiency with and willingness to use mobile devices anytime, anywhere. This study uses a randomized controlled trial design to investigate the impact of a digital app—ABCmouse English—on L2 learning of seven- and eight-year-old Japanese children over a 16-week period. Pre- and post-assessments of the children’s English proficiency, together with an analysis of when and how they played with the app, were used to shed light on the relationship between the children’s in-app game choices and their language learning outcomes. Surveys and interviews with parents provide qualitative insights and information about the experiences of children and their families while using the app and its impact on their development as language learners.